(untitled) (Orthodontic Journal of Nepal, 2025)
Impaction of second molar is a complex problem in orthodontics and its management can be very challenging. Intra-ramal bone screws provide traction forces in a superior and posterior direction, simplifying the mechanics and making uprighting of the mandibular molars highly efficient. This case report describes a 15-year-old male patient with impaction of second and third molars on lower left side of mandible. The second molar was trapped between the first and third molars and was overridden by the third molar. The impacted left mandibular third molar was extracted. At the same time, the crown of the second molar was surgically exposed and an attachment was bonded. The orthodontic traction was used to move and upright the second molar into its proper position by using intra-ramal bone miniscrew. At the end of treatment, the patient achieved an optimal occlusion and improved facial esthetics.